Desenvolvimento de parafuso de interferência bioabsorvível para cirurgia de joelho em PLDL (poli ácido lático) e compósito PLDL + βTCP (beta trifosfato de cálcio) - Santos, Alex Eugênio dos [UNESP] (2015)
The interference screw is the fixation device most selected for Knee ligament reconstruction surgeries. The use of Bioabsorbable polymers in interference screws for this application is increasing due it has advantages like excellent biocompatibility, bioabsorption, good integration between graft / bone and also facility in the surgical revision. The aims of the present study were to develop a bioabsorbable interference screw manufactured by the injection moulding process with two distinct polymeric materials: PLDL, Poly(L,DL-Latic acid) and a composite PLDL + 30% TCP (β Tricalcium phosphate). A program for structural analysis by finite elements was used in the development of the screw design, in the intend to make the best geometry fit for the tool. Trough the study by finite elements simulation it was possible to chose the geometry with higher mechanical resistance taking in the account the torsion effort and analyse the influence of transversals holes in the mechanical tensions made by the torque efforts. After the definition of the best geometry, samples of the screw were manufactured with the two selected polymers, sterilized with ETO (ethylene oxide). Were performed mechanical tests, insertion test and torque to break. The mechanical strenght of the screw was evaluated through the comparison between the values of insertion torque and maximum rupture. In addition, a in vitro, degradation test was performed over a period of 180 year days. It was observed, the weight loss, mechanical strength of the implants was evaluated, and molecular weight drops of the implants. Therefore it was possible to evaluate the mechanical behavior in degradation and compare with the application requirements. It can be observed that the raise of the molecular degradation of the implant along the months had as result a loss of the mechanical resistance of the screw, ina slowly and gradual way for the PLDL material, yet the composite material (PLDL+TCP)...